PERSEPSI MASYARAKAT TENTANG JASA TRANSPORTASI BERBASIS APLIKASI ONLINE DI KOTA MANADO (STUDI KASUS DI PT. GO-JEK) - MANUEKE, MANUELA; TAMPI, GUSTAAF BUDI; LONDA, VERY (Sam Ratulangi University, 2018)
Transportation is a very important field in the life of Indonesian society, considering the needs ofthe Indonesian community will be very high. Today the field of transportation in Indonesia is beingintensified with the emergence of transport-based applications or commonly referred to as online transport.Online transport is a transportation that utilizes the application as a media order to facilitate consumers interms of fulfilment of transportation needs. In 2011, standing online transportation company that until nowmuch talked about, that is Gojek. PT Gojek Indonesia is a private company based technology serviceprovider partnered with motorcycle riders in several cities in Indonesia, including Jakarta, Bogor, Bekasi,Bandung, Bali, Surabaya, and Manado. Management systems and operational mockery is to integratemodern start-up technology. Every driver using Android and GPS handphone with always-activeapplication, when customers order services through a gojek application, in a 3 km radius position, the callwill vibrate the connected driver phone until at last the reservation is fulfilled. Today, the ease offered byPT. Gojek Indonesia in meeting transportation needs has had a significant impact in some areas ofIndonesia. Some of the positive effects that gojek is given to the community is the cost of transportation thattends to be efficient, travel time is easy and participal, security is maintained when a passenger and get apolite service. The positive effects are highly appreciated by the public.Keywords: Public Perception, Transportation Service, Online Applications